2010
DOI: 10.3945/jn.110.127258
|View full text |Cite
|
Sign up to set email alerts
|

Ruminant-Produced trans-Fatty Acids Raise Plasma Total and Small HDL Particle Concentrations in Male Hartley Guinea Pigs ,

Abstract: Although trans-fatty acid (tFA) intake has been positively associated with coronary heart disease (CHD), the relative effect of consuming industrially produced (IP)- compared with ruminant-produced (RP)-tFA on CHD risk factors is unclear. This study was designed to examine the effects of feeding partially hydrogenated vegetable oil (PHVO), IP-tFA source, and butter oil (BO), RP-tFA source, on the development of atherosclerosis and risk factors associated with CHD. Forty-eight male Hartley guinea pigs were fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
3
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 41 publications
1
15
3
3
Order By: Relevance
“…Using these same test fats, we showed that when fed at a high level, IP-and RP-tFA had similar effects on traditional plasma cholesterol risk factors for CVD in male Hartley guinea pigs (14). In the guinea pig, however, RP-tFA, but not IP-tFA, resulted in increased levels of plasma total and small HDL particles, a particle profile that has been hypothesized to be associated with a decreased risk of CVD (14). Guinea pigs are an appropriate and often-used model for testing the effects of dietary interventions on established CVD risk factors because they have reverse cholesterol transport and metabolize lipoproteins similarly to humans (15).…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…Using these same test fats, we showed that when fed at a high level, IP-and RP-tFA had similar effects on traditional plasma cholesterol risk factors for CVD in male Hartley guinea pigs (14). In the guinea pig, however, RP-tFA, but not IP-tFA, resulted in increased levels of plasma total and small HDL particles, a particle profile that has been hypothesized to be associated with a decreased risk of CVD (14). Guinea pigs are an appropriate and often-used model for testing the effects of dietary interventions on established CVD risk factors because they have reverse cholesterol transport and metabolize lipoproteins similarly to humans (15).…”
Section: Introductionmentioning
confidence: 77%
“…Results also indicated that gender might play a role in the effects of IP-and RP-tFA intake on risk factors for CVD; RP-tFA raised plasma HDL-and LDL-cholesterol and large HDL and LDL particles in women, but not men, compared with IP-tFA. Using these same test fats, we showed that when fed at a high level, IP-and RP-tFA had similar effects on traditional plasma cholesterol risk factors for CVD in male Hartley guinea pigs (14). In the guinea pig, however, RP-tFA, but not IP-tFA, resulted in increased levels of plasma total and small HDL particles, a particle profile that has been hypothesized to be associated with a decreased risk of CVD (14).…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations